2019
DOI: 10.1002/mar.21290
|View full text |Cite
|
Sign up to set email alerts
|

Preventing shoplifting: Exploring online comments to propose a model

Abstract: In recent years, the marketing literature has expended considerable effort to understand and theorize consumer misbehavior. However, scant research theoretically explores shoplifting. This is surprising, as currently, the annual cost of shoplifting is close to $50 billion in the United States. Utilizing a mixed‐methods approach, we conduct two studies. Study 1 is a qualitative content analysis of online consumer discussions with regard to shoplifting. Study 2 is an empirical examination that uses a US national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Externalities are the uncalculated costs and benefits of exchange (Mundt 1993). Online reviews create a forum for consumer misbehavior but they also provide a means by which consumers can reflect on consumer misbehaviors (Korgaonkar et al 2020). With this exception, we found almost no substantive findings about the externalities related to online reviews.…”
Section: Online Reviews and Marketing System Effectivenessmentioning
confidence: 57%
“…Externalities are the uncalculated costs and benefits of exchange (Mundt 1993). Online reviews create a forum for consumer misbehavior but they also provide a means by which consumers can reflect on consumer misbehaviors (Korgaonkar et al 2020). With this exception, we found almost no substantive findings about the externalities related to online reviews.…”
Section: Online Reviews and Marketing System Effectivenessmentioning
confidence: 57%
“…Moreover, effective digital guardianship and online security management could lessen internet users' visibility from motivated offenders, thereby reducing the cybercrime victimization risk (Choi et al , 2019; Choi and Lee, 2017). Furthermore, internet users' exposure to potentially motivated offenders would change their attitude (Petrescu et al , 2018; Korgaonkar et al , 2019), which significantly influences the risk of crime victimization (Ellrich, 2016; Jansen and van Schaik, 2019). In particular, the MCMC’s report indicated that Malaysian young adults actively participate in social media for sharing and disseminating information (MCMC, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the cyber risky leisure and social media activities, it also increases the individual’s proximity to the motivated offenders and thus, more easily to be targeted by the offenders (Ngo et al , 2020; Choi, 2008). In the research field of shoplifting context, researchers noted that higher target suitability leads to one’s attitude change toward shoplifting (Korgaonkar et al , 2019). Thus, this study hypothesized that engaging in the cyber risky vocational activity leads to one’s attitude change, particularly attitude toward information sharing online.…”
Section: Recommendations For Phishing Prevention: the Importance Of A...mentioning
confidence: 99%
See 1 more Smart Citation
“…(Fullerton and Punj, 1993;Lugosi, 2019). The theory of planned behaviour (TPB) (Ajzen, 1991) can be considered an appropriate initial theoretical framework to guide UECB studies (Chang, 1998;Fukukawa, 2002;King et al, 2007;Potdar et al, 2017;Shaw et al, 2000;Shoham et al, 2008) as it identifies the various factors which influence the intention to perform UECB (Fukukawa et al, 2007;Korgaonkar et al, 2020). Given this and to better understand the UECB phenomenon in the Arab region, the current study set out to develop an advanced model of UECB for the Arabic consumer based on TPB (Ajzen, 1991) and the developed model of (Fukukawa et al, 2007) to determine the influences and motivating factors on UECB and rank these factors based on their strength of influence in the Arab consumers UECB adoption.…”
Section: Introductionmentioning
confidence: 99%